Implementing the WHO caregivers skills training program with caregivers of autistic children via telehealth in rural communities - Montiel-Nava, Cecilia; Tregnago, Megan; Marshall, Jeanne; Sohl, Kristin; Curran, Alicia Brewer; Mahurin, Melissa; Warne-Griggs, Melissa; , WHO CST Team; Dixon, Pamela (Frontiers in Psychiatry, 2022)
Background: For families with autistic children living in rural areas, limited access to services partly results from a shortage of providers and extensive travel time. Telehealth brings the possibility of implementing alternative delivery modalities of Parent Mediated Interventions (PMIs) with the potential to decrease barriers to accessing services. This study aimed to evaluate the feasibility and acceptability of implementing the World Health Organization-Caregivers Skills Training program (WHO-CST) via an online, synchronous group format in rural Missouri. Methods: We used a mixed methods design to collect qualitative and quantitative data from caregivers and program facilitators at baseline and the end of the program, following the last home visit. Caregivers of 14 autistic children (3-7 years), residents of rural Missouri, completed nine virtual sessions and four virtual home visits. Results: Four main themes emerged from the focus groups: changes resulting from the WHO-CST, beneficial aspects of the program, advantages and disadvantages of the online format, and challenges to implementing the WHO-CST via telehealth. The most liked activity was the demonstration (36%), and the least liked was the practice with other caregivers. From baseline to week 12, communication skills improved in both frequency (p<0.05) and impact (p<0.01), while atypical behaviors decreased (p<0.01). For caregivers' outcomes, only confidence in skills (p<0.05) and parental sense of competence (p<0.05) showed a positive change. Conclusion: Our results support the feasibility of implementing the WHO-CST program via telehealth in a US rural setting. Caregivers found strategies easy to follow, incorporated the program into their family routines, and valued the group meetings that allowed them to connect with other families. A PMI such as the WHO-CST, with cultural and linguistic adaptations and greater accessibility via telehealth- plays an essential role in closing the treatment gap and empowering caregivers of autistic children.